Impact of Migration on Women Empowerment: A Situational Analysis of North-Bihar - Kumari, Kalpana; Singh, K.M.; Ahmad, Nasim (Indian Journal of Extension Education, 2021)
The study was conducted during 2018-2019 to explore the impact of male migration in north-Bihar in empowering women in different domain of household decisions. Five domains namely agricultural production, asset creation, health care, educational decision of children and leadership were considered and women empowerment indices were computed for each domain. The result revealed that migration of male member adequately empowered only 29.44 % of women. Larger proportion of women respondents (43.89%) were found under moderately empowered category and 29.67% were observed still under low empowerment group. Women were adequately empowered in studied area to take decisions related to health care, education and agricultural production. The decision to purchase and sale of assets still was under the jurisdiction of male counterpart as the patriarchal system still dominated. The role of women in decision making in all the farm activities, from selection of crops to the sale of farm produce, showed comparatively more moderate empowerment indices. The paper concludes that the women are empowered to varying extent in situation of male migration from their native places.